Massive Open Online Courses in Public Health - Ira eGooding; Brian eKlaas; James D Yager; Sukon eKanchanaraksa (Frontiers Media S.A., 2013)
Massive open online courses (MOOCs) represent a new and potentially transformative model for providing educational opportunities to learners not enrolled in a formal educational program. The authors describe the experience of developing and offering eight MOOCs on a variety of public health topics. Existing institutional infrastructure and experience with both for-credit online education and open educational resources mitigated the institutional risk and resource requirements. Although learners are able to enroll easily and freely and do so in large numbers, there is considerable variety in the level of participation and engagement among enrollees. As a result, comprehensive and accurate assessment of meaningful learning progress remains a major challenge for evaluating the effectiveness of MOOCs for providing public health education.